Mergers and acquisitions case of: Arçelik and Ardem merger - Demirkaya, Bülent (My University, 1999)
After the global economic crisis that originated from Asia in the late 1998, the world economy has witnessed a spate of mergers and acquisitions; companies are joining together as never before. As the economy started to recover from crisis and, hence the recession, companies began to seek to expand and mergers and acquisitions once again, were seen as a quick and efficient manner in which to grow, instead of organic expansion. Besides the aim of reaching to sustainable growth, one of the most important motives behind the mergers of late 1998 and 1999 is cost cutting rather than other motives and determinants. Aided by the effects of the global crisis, the Turkish economy has been contracting since 1998 and there are signs that a recession is on horizon. To become less vulnerable to economical crisis, merger concept is put on the agenda of many domestic companies. However, rather than the developed countries, the concept of merger takes the shape of parent-subsidiary merger (usually for ones that are in the same lines of business). In contrast to conventional mergers, parent-subsidiary mergers do not entail arm's length barraging or a change in control. They facilitate corporate restructuring, foster reallocation of resources toward higher value uses, and increase value for both parent and subsidiary. The major motives of this type of mergers, in domestic market, are creating synergy by increase in purchasing power, cost savings in general administrative expenses, increase effectiveness of the operations by reducing repeating and lessening cost of capital. With-in this framework, Arçelik (white goods manufacturer of Koç Group) and Ardem (oven producer of Koç Group, a subsidiary of Arçelik) merged under Arçelik corporate control. This study proposes mergers and acquisition concept with recent motives and determinants as strategic management decision supported by valuation analysis of Ardem and Arçelik merger in the framework of anticipated existence of synergetic benefits. The Free-Cash-Flow-to-Firm model of discounted cash flow approach is used to analyze the benefits of the merger.

1998 senesi sonlarında Asya'da başlayan finansal kriz ile birlikte, Dünya ekonomisi önemli ölçüde şirket evliliklerine sahne olmaktadır; şirketler ekonomi tarihinde daha önce görülmemiş biçimde birleşmektedirler. Dünya ekonomisindeki krizin yavaş yavaş sona erip ekonomik küçülmenin iyileşmeye başlamasıyla, şirketler yeniden büyümek için evlilikleri, organik büyümenin yerine, daha çabuk ve verimli görmekte ve bu kapsamda arayışlara girmektedirler. Büyüme ile birlikte, maliyet düşürme hedefi, 1980 ve 1990lardaki evliliklerin en önemli sebebini oluşturmaktadır. Global krizin etkisiyle Türkiye ekonomisinde 1988'den itibaren bir daralma gözlenmekte ve bu bir resesyonun sinyallerini vermektedir. Krizler ve globalleşme ile küçülen pazar payları ile şirket birleşmeleri de Türkiye ekonomisinin gündemine girmiştir. Bununla beraber, gelişmiş ülkelerdeki birleşmelerin yanı sıra, Türkiye'deki şirket evlilikleri daha çok ana şirket iştirak evliliği şeklinde gerçekleşmektedir. Geleneksel şirket evliliklerin tersine, ana şirket iştirak evliliklerinin pazarlık bacağı bulunmamakla beraber, şirket kontrolü de değişmemektedir. Bu evlilikler, şirketlerdeki yeniden yapılanmayı ve kaynakların daha fazla katma değer yaratacak şekilde yönlendirilmesini kolaylaştırmaktadır. Türkiye'deki şirket evliliklerin en önemli amaçları, satın alma gücünü arttırıcı, maliyet azaltıcı, faaliyetlerin verimliliğini azaltıcı ve sermaye maliyetini düşürücü sinerjiler yaratmaktır. Bu kapsamda, Arçelik (Koç Grubunun beyaz eşya üreticisi) ve Ardem (Koç Grubunun fırın üreticisi), Arçelik bünyesinde birleşmişlerdir. Bu çalışma, şirket birleşmeleri kavramını, sebep ve sonuçları ile birlikte, stratejik yönetim kararı olarak ele alıp, bunların Ardem ve Arçelik şirket birleşmesinin değerlemesi (beklenen sinerjilerin oluşması öngörülerek) ile desteklenmesi üzerine yapılmıştır. İndirgenmiş nakit akışı yaklaşımı, birleşmenin beklenen yararlarını değerlemek için kullanılmıştır.
Keywords: Ekonomik Durum Türkiye